Bacterial Killing Activity of Polymorphonuclear Myeloid-Derived Suppressor Cells Isolated From Tumor-Bearing Dogs - Hlavaty, Sabina I.; Chang, Yu-Mei; Orth, Rachel P.; Goulian, Mark; Planet, Paul J.; Thamm, Douglas H.; Punt, Jennifer A.; Garden, Oliver A. (Frontiers in Immunology, 2019)
Polymorphonuclear myeloid-derived suppressor cells (PMN-MDSCs) are implicated in the progression and outcome of a variety of pathological states, from cancer to infection. Our previous work has identified three antimicrobial peptides differentially expressed by PMN-MDSCs compared to conventional neutrophils (PMNs) isolated from dogs, mice, and human patients with cancer. We therefore hypothesized that PMN-MDSCs in dogs with cancer possess antimicrobial activity. In the current work, we observed that exposure of PMN-MDSCs to Gram-negative (Escherichia coli) bacteria increased the expression of reactive oxygen species (ROS) by the PMN-MDSCs, indicating that they are capable of initiating an anti-microbial response. Electron microscopy revealed that the PMN-MDSCs phagocytosed Gram-negative and Gram-positive bacterial species. Lysis of bacteria within some of the PMN-MDSCs suggested bactericidal activity, which was confirmed by the recovery of significantly lower numbers of both kinds of bacterial species following exposure to PMN-MDSCs isolated from tumor-bearing dogs. Our data therefore indicate that PMN-MDSCs isolated from dogs with cancer, in common with PMNs, have phagocytic and bactericidal activity. This nexus of immunosuppressive and antimicrobial activity reveals a hitherto unrecognized function of MDSCs.